2011
DOI: 10.1089/met.2010.0121
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Hepcidin in Patients with Biopsy-Proven Nonalcoholic Fatty Liver Disease

Abstract: Although subject to future confirmation, our data suggest that hepcidin levels are elevated in NAFLD and could be associated with lipid parameters in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 22 publications
8
42
2
Order By: Relevance
“…This predominantly hepatic RES deposition in response to 2% carbonyl iron is consistent with a previous report (5). Increased serum hepcidin has also been associated with metabolic syndrome in humans (29). We also observed that the hepatic and adipose lipid metabolism was impaired in our DI mice.…”
Section: Discussionsupporting
confidence: 93%
“…This predominantly hepatic RES deposition in response to 2% carbonyl iron is consistent with a previous report (5). Increased serum hepcidin has also been associated with metabolic syndrome in humans (29). We also observed that the hepatic and adipose lipid metabolism was impaired in our DI mice.…”
Section: Discussionsupporting
confidence: 93%
“…A few recent studies have investigated hepcidin gene expression and/or circulating hepcidin levels in a small number of NAFLD patients with or without iron [33][34][35][36][37]. Bekri et al, found increased adipose (but not hepatic) tissue hepcidin mRNA levels were observed in obese individuals and correlated with IL-6 and CRP mRNA levels, suggesting that hepcidin was an adipokine upregulated in the chronic inflammatory state associated with obesity, however hepcidin expression was not different among obese subjects with NASH or diabetes [35].…”
Section: Hepcidin Is a Central Regulator Of Iron Homeostasismentioning
confidence: 99%
“…Aigner et al, showed that hepatic hepcidin expression was significantly higher in NAFLD subjects with hepatic iron staining compared to NAFLD subjects without iron and that hepcidin expression positively correlated with hepatic TNF-α expression and body mass index [33]. Several studies have investigated either urinary [34], plasma [37] or serum [36] hepcidin levels in patients with NAFLD compared to patients with other liver diseases or healthy controls. Subjects with Dysmetabolic Hepatic Iron Overload (DHIO, characterized by hepatic iron loading and features of the metabolic syndrome; 21/25 or 84% also had NAFLD) had significantly higher urinary hepcidin levels compared to NAFLD patients without hepatic iron, which the authors postulate may explain the predominantly mixed RES/HC iron distribution in this group [34].…”
Section: Hepcidin Is a Central Regulator Of Iron Homeostasismentioning
confidence: 99%
“…GH patients also display impaired hepcidin expression [33] . Although changes in both serum and liver hepcidin expression levels have been reported in NAFLD/NASH patients [14,[34][35][36][37][38] , the significance of hepcidin in disease pathogenesis is unknown. Our findings in this study with Hamp1 knockout mice administered a high fat diet for different time points suggest a role for hepcidin in NAFLD/NASH pathogenesis.…”
Section: Introductionmentioning
confidence: 99%